Administrators' technology leadership: Its influence on teachers' technology proficiency - Ma. Teresa E. Mendoza; Glenn Erick B. Catiis (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The educational system of the world has reached the 21st century. Teachers and principals have to adopt the immense changes brought by technological advancement. Teachers are equipped with 21st-century tools thanks to the administrators' technological expertise and their own; however, the intensity is only a possibility waiting to become a reality upon integration. At the height of the 2020 educational set-up brought about by the COVID-19 pandemic, the skills of positive technology integration for both administrators and teachers are needed to actualize and harmonize their respective areas. On this premise, a descriptive-correlational research design was conducted to assess the influence of administrators' technological leadership on teachers' technology proficiency in public high schools in the District of Bulakan and Sta. Maria, Bulacan, Philippines. It administered survey questionnaires to 16 administrators and 285 junior high school teachers during the school year 2020-2021. The data was analyzed using descriptive and inferential statistics. The results indicated that administrators possess a high level of technological leadership. This implies that they are ready and have full knowledge and practical know-how on the utilization and application of technology. On the other hand, teachers also possessed a high level of technological proficiency. This indicates that they are adept at utilizing technology to aid in the teaching and learning process. It comes to the conclusion that teachers' technological aptitude is not much impacted by administrators' technological leadership. This means that teachers can be more proficient; they upskill themselves since this is the demand of 21st century learning. Recommendation includes the implementation of educational reforms that support the new normal in education through programs that improve the quality of instruction and delivery, particularly during times of emergency or state calamity when classes are suspended or interrupted.